Expansion and Diversification of MFS Transporters in Kluyveromyces marxianus - Varela, Javier A.; Puricelli, Martina; Montini, Noemi; Morrissey, John P. (Frontiers in Microbiology, 2019)
In yeasts, proteins of the Major Superfamily Transporter selectively bind and allow the uptake of sugars to permit growth on varied substrates. The genome of brewer’s yeast, Saccharomyces cerevisiae, encodes multiple hexose transporters (Hxt) to transport glucose and other MFS proteins for maltose, galactose, and other monomers. For sugar uptake, the dairy yeast, Kluyveromyces lactis, uses Rag1p for glucose, Hgt1 for glucose and galactose, and Lac12 for lactose. In the related industrial species Kluyveromyces marxianus, there are four genes encoding Lac12-like proteins but only one of them, Lac12, can transport lactose. In this study, which initiated with efforts to investigate possible functions encoded by the additional LAC12 genes in K. marxianus, a genome-wide survey of putative MFS sugar transporters was performed. Unexpectedly, it was found was that the KHT and the HGT genes are present as tandem arrays of five to six copies, with the precise number varying between isolates. Heterologous expression of individual genes in S. cerevisiae and mutagenesis of single and multiple genes in K. marxianus was performed to establish possible substrates for these transporters. The focus was on the sugar galactose since it was already reported in K. lactis that this hexose was a substrate for both Lac12 and Hgt1. It emerged that three of the four copies of Lac12, four Hgt-like proteins and one Kht-like protein have some capacity to transport galactose when expressed in S. cerevisiae and inactivation of all eight genes was required to completely abolish galactose uptake in K. marxianus. Analysis of the amino acid sequence of all known yeast galactose transporters failed to identify common residues that explain the selectivity for galactose. Instead, the capacity to transport galactose has arisen three different times in K. marxianus via polymorphisms in proteins that are probably ancestral glucose transporters. Although, this is analogous to S. cerevisiae, in which Gal2 is related to glucose transporters, there are not conserved amino amino changes, either with Gal2, or among the K. marxianus galactose transporters. The data highlight how gene duplication and functional diversification has provided K. marxianus with versatile capacity to utilise sugars for growth.